Experimental investigation on strength and failure characteristics of cemented paste backfill-rock composite under uniaxial compression. (18th October 2021) - Wang, Yiren; Lu, Hongjian; Wu, Jie
Graphical abstract: Highlights: Cement paste backfill and rock composite samples with a rough interface, different interface dip angles and cement contents were made. Stress-strain curves, strength and failure patterns of CPB-R composite samples under uniaxial compression were investigated. Failure cracks evolution process of CPB-R composite samples was analyzed. Stress–strain response, strength and failure patterns depend on interface angle and cement content. Abstract: To investigate on the strength and failure characteristics of cemented paste backfill-rock (CPB-R) composite under uniaxial compression, specimen models of the CPB-R composite with nonlinear interface and different interface angles were proposed. Results show that stress-strain response, strength and failure pattern depend on interface angle and cement content. The brittleness stress-strain curve of composite consists of three parts: initial compaction, elastic and plastic yield stage. Besides, the brittleness-ductility and ductility stress-strain curves have an extra residual strength stage. The strength curve of composite first decreases and then increases with the increase of the interface angle, the strength of composite reaches the minimum when interface angle is 60° and the maximum when interface angle is 90°, which shows "V" shape. The failure modes of the composite with interface angle 0°, 15°, 30° are tensile and shear failure in the CPB. The damage areas of the composite with interface angle 45° and 60° extend from the CPB to the interface, their main failure mechanisms are shear failure. The failure processes of the composite with interface angle 75° and 90° are CPB damage first, but the final failure is controlled by the rock part. Their failure modes belong to tension-shear mixed failure.